Transfers, behavior change communication, and intimate partner violence: Postprogram evidence from rural Bangladesh - Roy, Shalini; Hidrobo, Melissa; Hoddinott, John F.; Ahmed, Akhter (MIT Press, 2019)
Transfer programs have been shown to reduce intimate partner violence (IPV), but little evidence exists on how activities linked to transfers affect IPV or what happens when programs end. We assess postprogram impacts on IPV of randomly assigning women in Bangladesh to receive cash or food, with or without nutrition behavior change communication (BCC). Six to ten months postprogram, IPV did not differ between women receiving transfers and a control group; however, women receiving transfers with BCC experienced 26% less physical violence. Evidence on mechanisms suggests sustained effects of BCC on women's “threat points,” men's social costs of violence, and household well-being.